Mujeres haciendo política trabajo político de mujeres en coaliciones de independientes: Movimiento Nuevo Perú y Alianza para el Progreso durante el período congresal 2016 -2019 - Villavicencio García, Laila Berenice (2021)
The research herein yields an account of the political work of women at “Alianza Para el Progreso” and “Movimiento Nuevo Perú” political organizations during the period 2018 – 2019. The purpose is to understand women’s motivations and incentives for which women venture into politics as well as their organizations’ institutional support to strengthen women’s participation. Gender and Political Science Studies are used as analytical perspectives for the research.